Plant pathogen‐mediated rapid acclimation of a host‐specialized aphid to a non‐host plant. Issue 21 (11th October 2021) - Ali, Farhan; Hu, Xiaoyue; Wang, Duoqi; Yang, Fengying; Guo, Hao; Wang, Yongmo
Abstract: Polyphagous aphids often consist of host‐specialized lineages, which have greater fitness on their native hosts than on others. The underlying causes are important for understanding of the evolution of diet breadth and host shift of aphids. The cotton‐melon aphid Aphis gossypii Glover is extremely polyphagous with many strict host‐specialized lineages. Whether and how the lineage specialized on the primary host hibiscus shifts to the secondary host cucumber remains elusive. We found that the hibiscus‐specialized lineage suffered high mortality and gave birth to very few nymphs developing into yellow dwarfs on fresh cucumber leaves, and did not inflict any damage symptoms on cucumber plants. The poor performance did not improve with prolonged exposure to cucumber; however, it did significantly improve when the cucumber leaves were pre‐infected with a biotrophic phytopathogen Pseudoperonospora cubensis . More importantly, the hibiscus‐specialized lineage with two‐generation feeding experience on pre‐infected cucumber leaves performed as well as the cucumber‐specialized lineage did on fresh cucumber leaves, and inflicted typical damage symptoms on intact cucumber plants. Electrical penetration graph (EPG) indicated that the hibiscus‐specialized lineage did not ingest phloem sap from fresh cucumber leaves but succeeded in ingesting phloem sap from pre‐infected cucumber leaves, which explained the performance improvement of the hibiscus‐specialized lineage on pre‐infected cucumber leaves. This study revealed a new pathway for the hibiscus‐specialized lineage to quickly acclimate to cucumber under the assistance of the phytopathogen. We considered that the short feeding experience on pre‐infected cucumber may activate expression of effector genes that are related to specific host utilization. We suggest to identify host‐specific effectors by comparing proteomes or/and transcriptomes of the hibiscus‐specialized lineage before and after acclimating to cucumber. Abstract : The hibiscus‐specialized Aphis gossypii cannot use cucumber as host plant but performed well on cucumber that has been pre‐infected with the phytopathogen Pseudoperonospora cubensis; a short feeding experience on the pre‐infected cucumber enables the hibiscus‐specialized A . gossypii to fully adapt to fresh cucumber.